Structure dependent activity and durability towards oxygen reduction reaction on Pt modified nanoporous gold. (1st March 2019) - Yu, Qingyang; Yin, Shuai; Zhang, Jian; Yin, Huiming
Abstract: Nanoporous gold (NPG) with three-dimensional bi-continuous structure have attracted many attentions ascribed to their desirable material characteristics, such as high surface area, high conductivity and outstanding chemical stability, especially for electrocatalysis. NPG-based electrocatalysts have exhibited notable properties towards oxygen reduction reaction (ORR), methanol oxidation reaction, formic acid oxidation reaction and related polymer electrolyte membrane fuel cells. In this work, structure dependent activity and durability towards ORR on NPG supported Pt (NPG-Pt) were investigated, because of the key roles of ORR in various applications such as fuel cell, metal-air batteries and H2 O2 generations. Typical NPG-Pt electrocatalysts with epitaxially monolayer, two-layer Pt shells and Pt nanoparticles were selected and systematically investigated relative to commercial Pt/C (20%, JM). The results reveal that all the NPG-Pt catalysts even the sample with only monolayer Pt i.e. Pt loading of 1.1 μg cm −2 mainly exhibit 4-electron ORR pathway without any H2 O2 yield, while commercial Pt/C with loadings lower than 2.4 μg cm −2 will favor H2 O2 generation which is harmful for the long-term stability. According to the performance stability, conventional accelerated degradation tests reveal that NPG-Pt with two-layer Pt shell (NPG-Pt2 ) exhibits the best stability ascribed to the strong metallic bond between Au and Pt. The mass ORR activity of this catalyst is almost unchanged (∼2% reduction) after 30000 cycles potential sweeping while the mass ORR activity of Pt/C with Pt loading of 20 μg cm −2 loses ∼60%. Therefore, NPG-based electrocatalysts present a good activity and stability than common nanoparticle electrocatalysts and developing nanoporous structure but cheap metal based electrocatalysts is a perspective way for cost reduction for commercial applications in energy storage and conversion field.